Bank-microfinance articulation in the development of the financial industry in central Africa - (:unkn) unknown (My University, 2021)
This thesis analyses the deepening of financial intermediation in Central Africa in a context of low financialinclusion, economic development and the magnitude of problems of access to finance for economic actors. Morespecifically, it highlights the need for banks and microfinance institutions (MFIs) in the Central African Economicand Monetary Community (CEMAC) to work together to meet the growing need for financial services offerings.Efficiency measures and articulation analyses in the context of financial system development are also provided.By proposing a way to improve added value in this area, this thesis makes an empirical contribution to this fieldof research, the results of which will serve to strengthen financial policy-making in Central Africa. The studyshows that banks and MFIs are essentially complementary in the CEMAC financial system and maintainarticulated relationship, despite the competition that is emerging as a result of some shifts from microfinance tothe banking segment. Also, the level of financial intermediation would be an ideal indicator of long-termeconomic growth in CEMAC; and there is a positive relationship between the microcredit indicator and growth,however weak. Finally, MFIs are not technically efficient in CEMAC, and make little use of innovative solutionsto develop their activities
Keywords: African Research